Pengaruh Motivasi Diri terhadap Peningkatan Kompetensi Kinerja Karyawan - Alifia Donna Soraya (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Self-motivation has been widely recognized as an important internal factor that encourages employees to continuously develop their competencies and improve workplace performance. Increasing organizational demands and competitive work environments require employees not only to possess adequate competencies but also to demonstrate a strong willingness to learn and adapt. This research employed a literature review approach by analyzing 20 scientific articles consisting of 10 international journals indexed by Scopus and 10 national journals indexed by Sinta. Data were examined through thematic analysis to identify patterns, relationships, and dominant findings regarding the role of self-motivation in competency development. The findings indicate that self-motivation contributes positively to the enhancement of employee competencies, particularly in improving technical skills, self-efficacy, creativity, professionalism, and work commitment. Several studies also reveal that the influence of self-motivation on performance becomes stronger when supported by adequate training, fair compensation systems, and conducive work environments. Although some studies report that motivation does not directly affect performance, competency development consistently emerges as a significant factor associated with employee effectiveness. These findings emphasize the importance of organizational strategies that strengthen employees’ self-motivation through career development opportunities, recognition systems, and continuous learning programs. Such efforts can support sustainable competency improvement and contribute to organizational performance enhancement.